An Insight into the Trigeminocardiac Re?ex- Understanding the Phenomenon and its Management - Manish Kumar Sharma; Archna Sharma (Asian Journal of Medical Research, 2021)
Trigeminocardiac reflex is a brainstem neurogenic reflex incited by stimulation of trigeminal nerve anywhere along its course from central nucleus to its peripheral distribution. Surgeries involving the craniomaxillofacial region may stimulate this reflex and complicates the procedure by manifesting as bradycardia, asystole, hypotension, apnoea and gastric hypermotolity. Thorough understanding of the pathophysiology, manifestations and ways of prevention and management of the trigeminocardiac reflex are of utmost importance for both the maxillofacial surgeon and the anaesthetist.